Prawo do swobody wypowiedzi a nieusuwalność i powoływanie sędziów – standardy demokratyczne Rady Europy - Derlatka, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The right to freedom of expression and the irremovability and appointment of judges - democratic standards of the Council of EuropeThe right expressed in Article 10 of the Convention stresses the importance of the freedom of expression and the freedom of information as the cornerstones of a democratic and pluralistic society. The main issue in this article is defining the limits of the freedom of expression enjoyed by judges in those circumstances when they are the authors of critical statements, not only when the critical opinions are addressed at judges and courts. The apolitical nature of judges means that their participation in a public debate on current political issues should be subject to special rules. The parent value of participation in a public debate is the special restraint. However, that does not change the fact that judges should comment on the current problems of the judicial system and the system of common courts. Judicial freedom of expression cannot be limited by a sanction threat violating the principles of the irremovability and appointment of judges.